Evaluación de lesiones y suturas vasculares por ultrasonografía peroperatoria - Terra, Freddy; Piazze, ALVAR; Vázquez, Enrique; Croci, Bettina; Kaitazzof, Pedro; Fernández, William (Cirugía del Uruguay, 1995)
A study on confiability and reproductability of vascular peroperative ultrasonography was carried out in dogs by making different types of lesions and vascular sutures. When evaluating the different procedures it was demonstrated that this non-invasive technique is use/u/, making it possible for the surgeon to evaluate the results of the surgical technique during surgery itse/f.